Some problems of legal regulation of financial control (Journal of actual problems of jurisprudence, 2018)
Financial control – a component, or the special branch, control exercised in the country. Existence of financial control is objectively caused by that to finance as economic category are inherent not only distributive, but also control in function. Therefore use by the state of finance for the solution of the tasks surely assumes carrying out with their help of control of a course of performance of these tasks. Financial control is exercised in the order established by rules of law by all system of public authorities and local governments, including special control bodies with the assistance of public organizations, labor collectives and citizens. Value of financial control is expressed that at its carrying out are checked, first, observance of the established law and order in the course of financial activity by the government and public bodies, the enterprises, establishments, secondly, economic feasibility of carried-out actions, compliance to their problems of the state.Key words: finance, finasovy policy, finasovy control, economy, budgetary policy, tax policy, monetary policy, etc.Keywords: finance, finasovy policy, finasovy control, economy, budgetary policy, tax policy, monetary policy, etc.Keywords: finance, finasovy policy, finasovy control, economy, budgetary policy, tax policy, monetary policy.